Polymerized stimuli-responsive microgels for the removal of organic dye from water - Pany, Biswajit; Majundar, Amrito Ghosh; Mohanty, Madhuchhanda; Fyis, K. P.; Dey, Tanima; Tripathy, Gautam; Bhat, Suresh; Yamanaka, Junpei; Mohanty, Priti S. (Journal of Molecular Liquids, 2023)
Polymerized hydrogel materials (PGM) containing uniform-sized stimuli-responsive microgel particles could be promising alternatives for solution-based microgels to remove organic dyes from water. In the current work, PGM is prepared using Poly(N-isopropylacrylamide-co-acrylic acid) based anionic microgels and their ability for uptake and release studies with an oppositely charged dye, methylene blue (MB) is carried out using UV-vis spectroscopy. The mechanism of dye adsorption is understood at a single particle level using light scattering, and zeta potential and the contributions from different molecular interactions among dye molecules and constituting entities of microgels are obtained from molecular docking studies. The maximum dye uptake by PGM is around 80 % in the swollen state (at pH 7 and 20 degrees C). In contrast, the dye release studies in the deswollen state (at pH 3 and 50 degrees C) show a decrease in the release efficiency from 87 % to 63 % of the total dye adsorbed in 4-repeated cycles. The adsorption isotherm follows a sigmoidal (S) model that has been majorly used in different multi-layer adsorption systems. Extensive dynamic and static light scattering studies demonstrate a deswelling of hydrody-namic radius and core-shell radius of microgels at low temperatures (20 degrees C) induced by dye adsorption. At higher temperatures, the dye-adsorbed microgels have a higher hydrodynamic radius than the pure microgels due to the remaining dye molecules within the microgel that do not release even in the deswollen state. Molecular docking studies show that electrostatic interaction dominates between COO- and MB and van der Waals/hydrophobic dominates for MB-NIPAM and MB-COOH docking complex respectively. Our work covering adsorption/desorption properties of the material to the single-particle level can provide a better understanding in formulating reusable smart materials for the remediation of different water pollutants.(c) 2023 Elsevier B.V. All rights reserved.
Keywords: dynamic light scattering; Molecular docking; PNIPAM microgels; Removal of organic pollutants; Stimuli -responsive microgels

Polymerized stimuli-responsive microgel hybrids of silver nanoparticles as efficient reusable catalyst for reduction reaction - Pany, Biswajit; Majumdar, Amrito Ghosh; Bhat, Suresh; Si, Satybrata; Yamanaka, Junpei; Mohanty, Priti S. (Heliyon, 2024)
We have showcased the potential of polymerized hydrogels (PGMs) with uniform -sized stimuliresponsive microgel particles as promising alternatives to prevent aggregation in solution based nanoparticle systems. In the current work, we implemented the PGM concept by embedding anionic stimuli -responsive microgels (PNIPAM-co-AAc)-silver (Ag) hybrids within a hydrogel matrix. These PGM@AgNP hybrid materials are used as catalysts for the reduction of 4-nitrophenol (4 -NP) to 4-aminophenol (4 -AP) in the presence of sodium borohydride. UV-VIS spectroscopy is used for studying catalytic activity. In the solution based system, the complete reduction of 4NP to 4 -AP took 30 minutes with pure Ag nanoparticles, 24 minutes with PNIPAM-Ag hybrid (Neutral) microgels and 15 minutes with PNIPAM-co-AAc-Ag (Anionic) hybrid microgels. In contrast PGM containing PNIPAM-co-AAc-Ag hybrids achieved full reduction in just 15 minutes, along with a 3 -minute induction period. For pure Ag nanoparticles, the first -order rate constant is found to be 0.25 min - 1, for PNIPAM-Ag hybrid (Neutral), it is 0.21 min- 1 and for PNIPAM-coAAc-Ag (Anionic), it is 0.5 min- 1 where as for PGM containing anionic microgel hybrids it is found to be 0.8 min - 1. Furthermore, the reusability of the PGM-Ag (anionic) materials for catalytic activity remains unaltered even after several washings. In summary, our study highlights the effectiveness of PGM@AgNP materials as efficient catalysts for the reduction of 4-nitrophenol to 4-aminophenol, indicating their versatile potential in various catalytic applications.
Keywords: Light scattering; Microgel-metal hybrids; Nanomaterial catalysts; PNIPAM microgels; Polymerized hydrogel matrix(PGM; Stimuli-responsive microgels